Unintended Consequences and Hidden Obstacles in Medicine Access in Sub-Saharan Africa - Barton, Iain; Avanceña, Anton L. V.; Gounden, Nevashini; Anupindi, Ravi (Frontiers in Public Health, 2019)
Many life-saving drugs are still inaccessible and unaffordable in most low- and middle-income countries, particularly in Sub-Saharan Africa. This contributes to poor health outcomes, wider health and socioeconomic inequities, and increased patient spending on healthcare. While resource limitations facing national regulatory authorities (NRAs) contribute to the problem, we believe that fragmented and complex drug regulations, suboptimal enforcement of existing regulations, and poorly designed disincentives for noncompliance play a larger role. These “unintended consequences” that are a direct result of our current regulatory regimes limit competition, keep drug costs high, and lead to shortages and the proliferation of illegitimate and unregistered drugs. While NRAs can gain a lot from increased investment in their work, innovation and regulatory harmonization can arrest and reverse the regulatory failures we still see today and improve medicine access in Africa. Unfortunately, regulatory harmonization initiatives in Sub-Saharan Africa have made modest impact and have done so slowly. We encourage greater attention and investment in regulatory harmonization and other downstream functions of NRAs. We also urge increased participation of national governments—particularly executive agencies in health and the treasury—and patient advocacy groups.